THE FINANCES OF THE CIVIL SOCIETY IN UKRAINE: KEY TRENDS, MODELS AND OBSTACLES IN ACHIEVING SUSTAINABILITY - Bidenko, Y. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The financial viability is one of the most important element in achieving sustainability for a civil society, especially in post-Socialist states of Eastern and Central Europe. Despite positive assessments of the role and potential of civil society in Ukraine from scholars and analysts and comparatively high score of civil society organizations’ sustainability index taking in comparative perspective for a whole region, its financial capabilities remains its weakest part during decades of Ukrainian independence. Having comparatively friendly legal and political environment and achieving some impressive results in advocacy, building coalitions and networks and enhancing its organization capabilities Ukrainian CSOs still remain dependant from international donors. Some shifts in financial resilience of civil society demands not only efforts from its side, but finding a consensus with a state on the model to achieve.Three typical models of interrelations by civil society and government, emerged in contemporary Europe are provided, they could be distinguished based on the social and political role of CSOs and their functions in public services provision. These models based on the scales of institutionalization and level of independence of civil society relatively to the authorities and include Social-democratic (Scandinavian), Liberal (Anglo-Saxon) and Corporativism (Continental) types. Ukrainian civil society, regardless achievements in organizational capacities and sectoral infrastructure, still remains in the «emerging» transitional spot due to the extremely small amount of public funds it attracts and based on uncertainty of its role on national and local level.Perspective destinations for civic-state dialogue are emphasized, among which there are finding the consensus of desired model and adopting new National Strategy of Stimulation Civil Society in Ukraine for next five years, changes in legal framework for local self-government, social entrepreneurship, taxation of charity and means earned by CSO themselves and establishing new practices and institutions for public financing of CSOs on national and regional levels.